Exploring ethical principles amongst practicing community pharmacists in Portugal: any reasons for concern? - Cavaco, Afonso Miguel (2023)
Pharmacists facing ethical dilemmas have shown weaknesses in principled reasoning and disclosure. The chapter describes research on Portuguese community pharmacists' moral reasoning and narrative ethics. A cross-sectional survey comprising vignettes with practice ethical dilemmas, their possible justifications, and an open box for textual accounts was used as the research tool. More than 270 pharmacists replied, primarily young (<35 years old) female practitioners and 75% were involved in direct contact with patients. At least 50% of the sample showed compliance with the expected ethical-based decisions, except for the non-maleficence principle (10.9%); although receiving the highest proportion of the corresponding justification (30.3%), no open accounts or narratives were registered. The present findings suggest ethical passivity associated with decision-making in practice and a potential conflict between the clinical and the business roles. Explicit ethical norms for practice guidance and additional moral reasoning and narrative training are suggested.